A Model of Transformational Leadership in the Organisational Culture of Preschool Institution - Vesnica Mlinarević; Ružica Tokić Zec; Ana Cvjetičanin (Center for Educational Policy Studies Journal)
The culture of an organisation refers to the common and dominant values and norms, as well as the beliefs and perceptions of its employees. Organisational culture influences employee behaviour and attitudes. The culture of the institution predetermines the tone of the environment, which can affect employee satisfaction. The basic premise of this paper is established in the connection between the characteristics of the leader and the transformational model of leadership in the organisational culture of the preschool institution. This research aims to determine whether the assessments and self-assessments of leaders and preschool teachers differ in the frequency of using the transformational leadership style and to determine the relationship between the transformational leadership style and the leader’s personality traits. The research was conducted in a private Croatian preschool institution, which consists of 10 kindergartens. A total of 51 participants in 9 kindergartens participated in the research. The study used a quantitative research approach. The research results show that preschool teachers and leaders do not differ significantly in estimates of the frequency of application of the transformational leadership style and that there is a significant correlation between some characteristics of the leader and the transformational model of preschool leadership.